ANALISIS BUTIR SOAL KETRAMPILAN BERFIKIR TINGKAT TINGGI SISWA XI PADA MATERI SISTEM GERAK MANUSIA - Ningrum, Sevyani Widya; jumrodah, jumrodah; Lestari, Sri (Program Studi Pendidikan Biologi FKIP Unpatti, 2023)
Background: One of the skills that students should be have is higher-order thinking skills, especially critical thinking skills acquired during learning which are measured to find out student learning outcomes in the form of tests. Before the test, an analysis of the quality of the test or item analysis is carried out to produce a quality test and meet the test requirements, namely validity, reliability, objectivity, index of difficulty, and discriminatory power. Methods: This research uses a quantitative descriptive approach Results: The research showed that the results of the instrument for testing higher-order thinking skills, especially critical thinking skills in the subject of human movement systems for class XI students at MA Darul Ulum, were declared valid and reliable, then used to measure higher-order thinking skills. The average score of students' higher-order thinking skills for the descriptive item test instrument was 72. The highest score for the descriptive item test instrument achieved by students was 96 and the lowest score was 32. This shows that students' higher-order thinking skills were still lacking. The researcher re-developed the high-order thinking skills test instrument by adjusting the performance indicators to the questions. Conclusion: The test instrument for higher order thinking skills, especially critical thinking skills in the human movement system material for class XI students at MA Darul Ulum which was developed is valid, reliable, and feasible to use.